URGENSI HUMAN RESOURCE MANAGEMENT DALAM MENCIPTAKAN KEUNGGULAN BERSAING PADA BISNIS DI ERA KONTEMPORER - Suparwi Suparwi (Bussman Journal : Indonesian Journal of Business and Management, 2021)
Today's era of globalization, companies are required to be able to compete with competitors who of course not only come from within the country but also have to compete with competitors from abroad. This increasingly fierce competition makes business people must have quality human resources so that they have a good production process so that company productivity can be realized. Human resources are the key in every organization, the implementation of proper human resource management will make the company's research capability a competitive advantage for the company. which in turn will become a valuable long-term asset for the company. Although the role of human resources management in carrying out business activities is not as extensive as in the past, the role of human resources is quite significant and sometimes cannot be replaced in certain domains. Therefore, human resources should be managed according to their function so that they are always productive and generate more profit for the company. The trend of human resource management in the contemporary era provides a new paradigm by using information technology, so it is very helpful in managing existing human resources for companies